Carburization Analysis of Ethylene Pyrolysis Furnace Tubes after Service. (2015) - Lian, X.M.; Chen, X.D.; Chen, T.; Ye, J.; Sun, J.F.
Abstract: Carburization of 34 pieces of 25Cr35NiNb+MA and 17 pieces of 35Cr45NiNb+MA ethylene pyrolysis furnace tubes with different service time from 6 petrochemical enterprises were detected. The detection included C content test at inner-wall, the macrostructure of tubes after etching, observation of microstructure and Vickers hardness test. The detection results showed that in 34 pieces of 25Cr35NiNb+MA alloy furnace tubes, carburized layer thickness of 11 pieces tubes with the service time less than 3 years were not exceed 60% of the wall thickness (the replacement threshold value of ethylene pyrolysis furnace tubes), in 23 pieces of furnace tubes with service time about 4∼7 years, the maximum thickness of carburized layer of 8 pieces of furnace tubes were more than 60% of the wall thickness. In 17 pieces of 35Cr45NiNb+MA alloy furnace tubes, carburized layer thickness of 1 piece of furnace tube with service time about 9 years was exceed 60% of the wall thickness. The detection results and resistance of carburization of furnace tubes were discussed in this paper.